The intervening effect of the earning quality on dividend policy and financial performance in food and beverage manufacturing - Miswaty Miswaty (INOVASI, 2022)
This study aims to examine the relationship between dividend policy influences financial performance with earning quality as intervening  variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange 2016-2018. The technique of data analysis method used in this study is path analysis to explain the relationship between variables of company dividend policy, earning quality and financial performance. The results showed that company dividend policy had a significant effect on financial performance through intervening  earning quality. From the conclusions, the researcher provides suggestions to pay attention to the factors that influence the financial performance so that it can be used as a consideration in decision making and can be used as material to evaluate and improve the company's management performance in the future so that it can become an attraction for investors in investing in companies.